Sino- India Soft Power Diplomacy Towards Southeast Asia: A Comparative Analysis - Kumar, Naresh and Kashyap, Vimal Kumar (Indian Journal of Political Science)
Joseph Nye's concept of soft power has gained traction in both India and China in recent years, In terms of Southeast Asia, India and China both, due to their cultural and historical similarities, geographic proximity, and geostrategic reasons, are in the process of increasing, promoting, and wielding their respective soft powers. Therefore, the present paper attempts to look into the deployment or application of soft power diplomacy by India and China in relation to Southeast Asian countries. The principal object of the present paper is to make a comparative analysis of Sino- Indian soft power diplomacy towards Southeast Asia from 2014 to 2021. The paper examines the different resources of Sino- India soft power diplomacy in Southeast Asia, notably culture, diaspora, vaccine diplomacy, and education. This research paper also examines the perceptions of Southeast Asian countries towards the Sino- India soft power diplomacies. Furthermore, the paper examines how India's soft power diplomacy has advantage over China's soft power diplomacy towards the Southeast Asian region. - Reproduced
Keywords: India, China, soft power diplomacy, Southeast Asia